2011
DOI: 10.1111/j.1365-2966.2011.19278.x
|View full text |Cite
|
Sign up to set email alerts
|

Integral field spectroscopy of selected areas of the Bright bar and Orion-S cloud in the Orion nebula★

Abstract: We present integral field spectroscopy of two selected zones in the Orion nebula obtained with the Potsdam Multi‐Aperture Spectrophotometer, covering the optical spectral range from 3500 to 7200 Å and with a spatial resolution of 1 arcsec. The observed zones are located on the prominent Bright bar and on the brightest area at the north‐east of the Orion south cloud, both containing remarkable ionization fronts. We obtain maps of emission‐line fluxes and ratios, electron density and temperatures, and chemical a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 59 publications
(134 reference statements)
4
24
0
Order By: Relevance
“…The fact that the abundances are not constant across the nebula but show a certain degree of structure has already been discussed in (Mesa-Delgado et al 2011, henceforth referred to as MD11) and Núñez-Díaz et al (2012). Specifically, MD11 find that for the BB their mean value of 8.49 ± 0.03 for the O/H ratio agrees with previous estimates of 8.50 (e.g.…”
Section: Ionic and Total Abundancessupporting
confidence: 57%
See 2 more Smart Citations
“…The fact that the abundances are not constant across the nebula but show a certain degree of structure has already been discussed in (Mesa-Delgado et al 2011, henceforth referred to as MD11) and Núñez-Díaz et al (2012). Specifically, MD11 find that for the BB their mean value of 8.49 ± 0.03 for the O/H ratio agrees with previous estimates of 8.50 (e.g.…”
Section: Ionic and Total Abundancessupporting
confidence: 57%
“…Peimbert & Torres-Peimbert 1977;Baldwin et al 1991;Rubin, Dufour & Walter 1993;Esteban et al 1998;Sánchez et al 2007;Mesa-Delgado et al 2011), and it serves as the comparison ground for abundances in other extra-and Galactic H II regions. One of the major problems in determining abundances is the dependence of line emissivity on the electron temperature T e : the emissivity of recombination lines (RLs) decreases with increasing T e , while the emissivity of collisionally excited lines (CELs) increases with T e in an exponential manner (O'Dell 2001).…”
Section: Ionic and Total Abundancesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the moment, however, this improved dataset is not publicly available in reduced form. Additionally, there are several studies with very good data quality in terms of depth, spectral, and spatial resolution devoted to the study of invidiual targets within the Orion Nebula that observed the interplay of gas and stars in proplyds and Herbig-Haro objects (e.g., Vasconcelos et al 2005;Mesa-Delgado et al 2011Tsamis & Walsh 2011;Tsamis et al 2013;Núñez-Díaz et al 2012). Therefore, they only mapped very small (∼10 ) rectangular areas.…”
Section: Introductionmentioning
confidence: 99%
“…), making the O + + H 2 channel a likely source of OH + at low depths. Detailed comparison of the optical and near-IR (forbidden and/or permitted) lines of O and O + would be a stronger test of this scenario (Walmsley et al 2000;Mesa-Delgado et al 2011). In addition, simulations of the full molecular + atomic + ionized gas in the Orion PDR with the Cloudy program (Ferland et al 2013) would be useful to constrain the role of possible ion sources in the Orion Bar.…”
Section: Possible Ion Sourcesmentioning
confidence: 99%